The Types and Causes of Misconceptions about the Circulatory System in Madrasah Ibtidaiyah Negeri of Pontianak City - Segara, Angga Bayu; Kartini, Kartini; Setyaningrum*, Vidya (Universitas Syiah Kuala, 2024)
The background of this study arose from the need to identify and overcome barriers to understanding crucial concepts in the human circulatory system. This study aims to describe the profile of students misconception about the blood circulatory system and their causes in MIN-Kota Pontianak consisting of MIN 1 Pontianak City, MIN 2 West Pontianak, MIN 3 Southeast Pontianak and MIN 1 Filial East Pontianak. The research method used a descriptive quantitative approach with a population of all grade VI students. Sampling was done with a proportionally stratified random sampling technique. Data collected using two-tier tests and semi-structured interviews. The research showed that misconception rate in Madrasah Ibtidaiyah throughout Pontianak City is 47.3%. Results also showed that students' misconception profile consists of: a) incorrect understanding of the role of the lungs. b) The function of the foyer and the chambers of the heart. c) incorrect understanding of the difference in the function of blood vessels in the heart and throughout the body. d) incorrect understanding of the role of capillary vessels in the circulatory system. The causes of misconceptions are: a) Inaccurate or inappropriate sources of information, b) The lack of clarity of concepts in the delivery of the material, c) The continuation of the previous class's understanding, d) Random answers or guessing also play a role in the occurrence of misconceptions.